User Identification System Based On Finger-Vein Patterns Using Convolutional Neural Network - Syazana Itqan, Khalid; Syafeeza, Ahmad Radzi; Gong, Fook Guan; Nur Badariah Ahmad, Mustafa; Wong, Yan Chiew; M. M., Ibrahim (Asian Research Publishing Network (ARPN), 2016)
Finger-vein biometric identification has gained attention recently due to its several advantages over fingerprint biometric traits. Finger-vein recognition is a method of biometric authentication that applies pattern recognition techniques based on the image of human finger-vein patterns. This paper is focused on developing a MATLAB-based finger-vein recognition system using Convolutional Neural Network (CNN) with Graphical User Interface (GUI) as the user input. Two layers of CNN out of the proposed four-layer CNN have been used to retrain the network for new incoming subjects. The pre-processing steps for finger-vein images and CNN design have been conducted pm different platforms. Therefore, this paper discusses the method of linking both parts from different platforms using MEX-files in MATLAB. Evaluation is carried out using images of 50 subjects that are developed in-house. An accuracy of an average of 96% is obtained to recognize 1 to 10 new subjects within less than 10 seconds.